The prognostic value of phospholipase A2 receptor autoantibodies on spontaneous remission for patients with idiopathic membranous nephropathy: A meta-analysis. Issue 23 (June 2018) - Wu, Wenli; Shang, Jin; Tao, Chenyang; Wang, Shuai; Hu, Xiaoru; Zhang, Shiyi; Zhao, Zhanzheng
Abstract: Background: The presence of antibodies against phospholipase A2 receptor (PLA2R-Abs) in serum at diagnosis is reported to be related to the rate of spontaneous remission in patients with idiopathic membranous nephropathy (IMN); however, there is still lack of enough samples to illustrate this problem. Here, we conducted a comprehensive meta-analysis to investigate the prognostic value of PLA2R-Abs on spontaneous remission for IMN patients in the absence of immunosuppressive therapy. Methods: A systematic search of the PubMed, EMBASE, and Cochrane Central databases was performed for relevant original articles published until October 2017. All studies focus on spontaneous remission rates in IMN patients associated with PLA2R-Abs, the endpoint of interest is spontaneous remission rate. Risk ratio (RR) and corresponding 95% confidence intervals (CI) were carried out using a fixed or random effects model. The data were analyzed by Review Manager 5.3 software. Results: A total of 5 articles involving 190 patients were included in this meta-analysis. There were significant differences between the 2 groups in spontaneous remission rate. The seropositive of PLA2R-Abs measured at the time of diagnosis was negatively correlated with the likelihood of spontaneous remission (RR = 0.69; 95% CI, 0.56–0.87; P  = .001). Conclusion: In PLA2R-Abs seronegative patients, the spontaneous remission rate is higher than that of PLA2R-Abs seropositive patients during symptomatic treatment. Therefore, in order to avoid malignant events caused by immunosuppressive therapy, maybe it is more beneficial to adopt conservative treatment for PLA2R-Abs seronegative patients at initial treatment.